Fassin D. (2013) Enforcing Order: An Ethnography of Urban Policing. Cambridge: Polity. 320 p. - Корбут, Андрей (Социологическое обозрение, 2014)
Fassin D. (2013) Enforcing Order: An Ethnography of Urban Policing. Cambridge: Polity. 320 p. ISBN 978-0-7456-6480-4